Robust stochastic sampled-data control for offshore steel jacket platforms with non-linear perturbations. (11th September 2015) - Sivaranjani, K.; Rakkiyappan, R.; Lakshmanan, S.; Lim, C. P.
Abstract: This paper deals with the problem of robust exponential stabilization of offshore steel jacket platforms, where linear fractional uncertainties and randomly occurring uncertainties are taken into account. In this work, we introduce a sampled-data controller with $m$ stochastically varying sampling intervals whose occurrence probabilities are given constants and satisfy Bernoulli distribution. A discontinuous type Lyapunov–Krasovskii functional with triple integral terms based on the extended writinger's inequality is constructed and some sufficient conditions that guarantee the exponential stabilization of considered system are derived in terms of linear matrix inequalities by using Jensen's inequality and reciprocally convex technique. Finally, a numerical example is presented to show the effectiveness of the proposed results.